Report of the Executive Committee of the Programme of the United Nations High Commissioner for Refugees on the Sixty-fifth session (29 September to 3 October 2014) - United Nations (United Nations, 2014)
This is the official record of the Executive Committee of the Programme of the United Nations High Commissioner for Refugees on the Sixty-fifth session (29 September to 3 October 2014)